Interactive carbon priming, microbial response and biochar persistence in a Vertisol with varied inputs of biochar and labile organic matter. (29th April 2019) - Fang, Yunying; Singh, Bhupinder P.; Nazaries, Loïc; Keith, Alexander; Tavakkoli, Ehsan; Wilson, Neil; Singh, Balwant
Abstract : There has been great interest in biochar application to soil for long‐term carbon (C) sequestration. However, the interactive priming of organic C mineralization, including shifts in microbial community structure and the persistence of biochar in a clayey soil amended with biochar and labile organic matter (LOM) over a relatively long period (i.e. years) remain poorly understood. A 2‐year incubation study was carried out with δ 13 C‐depleted biochars produced from Eucalyptus saligna Sm. wood biomass at 450 and 550°C. Each of the biochars (at 2%, w/w) in combination with LOM, such as sugarcane residue at input rates of 0, 1, 2 or 4% w/w, were mixed with a C4 ‐dominated Vertisol. The interactive effect of biochar and LOM on the structure of the microbial community was analysed by terminal restriction fragment length polymorphism (T‐RFLP). Our results showed that at the small LOM rates (0 and 1%), there was a positive priming effect of biochar on organic C in soil (i.e. native soil organic C (SOC) + LOM‐C)), which shifted to being negative when the LOM input was increased to 2 or 4%. Over the 2 years, mineralization of C from the 450°C biochar (1.2–1.7%) was significantly greater than that for 550°C biochar (0.6–1.0%), and the positively primed mineralization of biochar‐C by LOM was enhanced by the increasing rates of LOM input. The negative priming of native SOC + LOM‐C mineralization by biochar was greater at large than small inputs of LOM, which would have been facilitated by greater shifting in fungal communities, while enhancing biochar‐C mineralization and possibly soil aggregation. In conclusion, over the long term, the amount of LOM stabilized by biochar was greater than that of positively primed biochar‐C mineralization by LOM, in particular at the large LOM input. Biochar can persist in soil on a centennial scale and decreases the turnover of native SOC + LOM‐C over the long term, whereas LOM input can shift microbial communities, favouring LOM stabilization in the biochar‐amended Vertisol. Highlights: Do C priming, biochar persistence and microbial response change 2 years after biochar–LOM inputs? Examined interactive C priming (stable‐C isotope), microbial community structure and biochar MRT. Priming of SOC ± LOM‐C by biochar and vice‐versa increased with LOM inputs. Biochar–LOM interaction (2‐year) shifted microorganisms, favouring LOM‐C stabilization in a Vertisol.